Writing business proposals and reports : strategies for success - Brock, Susan L. (Crisp Pub. Menlo ParkUS, 1992)
Provides strategies and methodology for writing business reports and proposals. Addresses concerns such as: punctuation, organization, style, tone, and editing. Samples of the persuasive report, feasibility study, and business proposal are provided.